Cultivar-dependent variation in food-feed-traits in groundnut (Arachis hypogaea L.) - Nigam, S.N.; Blümmel, Michael (2010)
A total of 860 cultivars and breeding lines of groundnut grown in the off (Rabi) season of 2001/02 post rainy season at ICRISAT centre head quarter in India were investigated for haulm fodder quality traits and relationships between haulm traits and pod yields. Haulm fodder quality traits chosen were nitrogen (N x 6.25 equals crude protein), in vitro digestibility and in vitro metabolisable energy content. The haulm fodder quality traits were analyzed by a combination of conventional laboratory techniques and Near Infrared Reflectance Spectroscopy (NIRS). Significant (P<0.0001) and livestock nutritionally important cultivars differences were found for all three traits. Thus haulm nitrogen content ranged from 1.2 to 2.3%, in vitro digestibility ranged from 51.7 to 61.1%, and in vitro metabolisable energy content ranged from 6.9 to 8.8 MJ/kg. No inverse relationships were observed between any of the haulm fodder quality traits and pod and haulm yields. Haulm fodder quality analysis was repeated for 12 check cultivars in 2002 and over the two years broad sense heritabilities (h2) for nitrogen, in vitro digestibility and in vitro metabolisable energy content were 0.72., 0.72 and 0.67, respectively. The findings of the present study suggest that pod yield, haulm yield and haulm fodder quality traits can be simultaneously improved to develop better dual purpose groundnut varieties.